A phase I, open‐label, single‐dose study to evaluate the effect of hepatic impairment on the pharmacokinetics and safety of futibatinib - Ling Gao; Ikuo Yamamiya; Mark Pinti; Juan Carlos Rondon; Thomas Marbury; Gareth Tomlinson; Lukas Makris; Nanae Hangai; Volker Wacheck (Wiley, 2023)
Abstract Futibatinib is a covalently binding FGFR1-4 inhibitor that received US Food and Drug Administration approval for the treatment of patients with previously treated, advanced intrahepatic cholangiocarcinoma harboring FGFR2 gene fusions/rearrangements. This phase I trial evaluated the pharmacokinetics (PKs), safety, and tolerability of futibatinib in subjects with impaired hepatic function and matched healthy volunteers. Twenty‐two subjects with hepatic impairment (8 mild [Child‐Pugh 5-6], 8 moderate [7-9], and 6 severe [10-15]) and 16 matched healthy control subjects received a single oral dose of futibatinib 20 mg. Futibatinib PKs were compared between subjects with mild/moderate/severe hepatic impairment and each corresponding control cohort and the overall control cohort. Relationships between futibatinib PKs and Child‐Pugh scores and liver function tests were examined via scatter/regression plots. Compared with matched controls, the area under the plasma concentration-time curve from time zero to infinity increased by 21%/20%/18% and the maximum plasma concentration (Cmax) increased by 43%/15%/10% in subjects with mild/moderate/severe hepatic impairment, respectively. Changes were not considered clinically relevant: geometric mean ratios were within 80%-125%, except for Cmax in subjects with mild hepatic impairment (143%). No obvious trends were observed among futibatinib PK parameters versus Child‐Pugh scores, bilirubin, albumin, international normalized ratio, and aspartate aminotransferase (all p > 0.05). Futibatinib was well‐tolerated, with only four grade 1 treatment‐emergent adverse events (mild hepatic impairment = 2 and control = 2). The results demonstrate that futibatinib dose adjustments due to mild/moderate/severe hepatic impairment are not necessary in patients receiving futibatinib 20 mg daily.